The Frente de Todos government, or the failure of the search for the impossible consensus - Cantamutto, Francisco (Papel Político, 2024)
This article analyzes the arrival of the Frente de Todos government in Argentina in 2019, as part of a second cycle of progressive or popular governments in the region. After the neo-developmentalist experience of Kirchnerism, the country experienced a government with neoliberal policies (with the Cambiemos coalition) that plunged it into a severe crisis, to which was added the one generated by the pandemic. The government of the Frente de Todos promised to generate a process of growth with redistribution, but was unable to do so. This article, based on a political economy perspective, argues that the underlying reason lies in the government's consensual emphasis, which sought to avoid the re-foundational intentions of one part of the coalition, namely Kirchnerism itself. The intention of agreeing even with the winners of the previous period limited the possibilities of acting in pursuit of a redistributive process or structural change, thus limiting the margins for action. Faced with the lack of economic results, but also in the biases of the management of the pandemic, a radical right-wing criticism grew in the opposition, which modified the political scenario.